The Role of Material and Moral Incentives on the Efficiency of the Performance of Health Personnel - Al-Rashidi, Khaled Sharie; Al-Anzi, Sultan Ayed; Al-Nassar, Muhammad Jalal; Al-Rashidi, Saud Obaid; Al-Rashidi, Sultan Obaid; Nassar, Hammoud Jalal (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the reality of material and moral incentives in the government health sector in the Kingdom of Saudi Arabia, as well as to identify the relationship between material and moral incentives and the performance efficiency of health cadres in hospitals in Riyadh. The study used the descriptive analytical method, and the study sample amounted to (112) workers in government health institutions in Riyadh, the study used a questionnaire as a tool for data collection. The problem of the study was the importance of what material and moral incentives play and their great role in influencing the efficiency of the performance of workers, whether positively or negatively, which means that they are not available and not distributed in a fair way that may be reflected on the performance of health cadres in health institutions. Where the study (Al-Qadas, 2017) indicated that there is a positive relationship to material and moral incentives on the performance of workers in private hospitals in Jordan, so the study problem came in the following question, what is the role of material and moral incentives on the efficiency of the performance of health personnel, as the study assumed the existence of a statistically significant relationship Between the material and moral incentives and the efficiency of the performance of health cadres in hospitals in the city of Riyadh. By answering the question of the study problem and confirming the hypothesis of the study, suggestions will be presented that contribute to raising the efficiency of the performance of health cadres working in government sector hospitals in the Kingdom of Saudi Arabia through attention and the development of policies for material and moral incentives in the health system. In light of the foregoing, the study reached a number of results, the most important of which is the existence of a direct statistically significant relationship between material and moral incentives and the performance efficiency of health cadres, where the value of the Pearson correlation coefficient (0.575), which is a statistically significant value at the level of significance (0.05). In light of the results of the study, the researchers recommend the following: The need to be aware of the concept of material and moral incentives because of its benefits on the efficiency of performance for workers in health institutions. The need to enhance the material and moral incentives granted to health cadres in the government health sector in the Kingdom of Saudi Arabia through an integrated and effective system that works to grant incentives to those who deserve it according to the efficiency of performance. Granting promotions according to outstanding performance and not relying solely on seniority.